Kelimpahan Populasi dan Tingkat Parasitisasi Parasitoid Indigenus terhadap Hama Invasif Liriomyza trifolii (Burgess) (Diptera: Agromyzidae) pada Tanaman Asteraceae di Bali - I WAYAN SANDIKA YASA; I WAYAN SUPARTHA; I WAYAN SUSILA (Agrotrop : Journal on Agriculture Science, 2020)
Population Abundance and Parasitization Level of Indigenous Parasites to Invasive Liriomyza trifolii (Burgess) (Diptera: Agromyzidae) on Asteraceae Plants in Bali. This study was aimed to determine the population abundance and parasitization level of indigenous parasitoid associated with Liriomyza trifolii (Burgess) in Asteraceae plants in Bali. The study was conducted from January to March 2019 by survey method on the type of parasitoid, abundance and parasitisation level in Asteraceae plants which included to Chrysanthemum, Gerbera jamesonii and Helianthus annuus, which are spread in several regencies in Bali such as Buleleng (1200 m asl), Bangli (900-1000 m asl) and Denpasar (40 m asl). Sampling was done purposively on the leaves of plants attacked by Liriomyza sp. and then maintained at the Laboratory until the parasitoid adults appeared. Afterward, morphologically was identified the type of parasitoid that appears. The results showed that there were three types of indigenous parasitoid associated with L. trifolii namely Hemiptarsenus varicornis, Neochrysocharis okazakii, and Opiusdissitus. The most dominant parasitoid of the three types of H. varicornis parasitoid with an abundance of 78.57% and parasitization rate of 53.23% was found in Chrysanthemum plants.